The first damselfly (Odonata, Lestidae) from the upper Eocene of Monteils (Gard, France) - Jattiot, Romain; Latutrie, Benjamin; Nel, André (Zootaxa, 2020)
The discovery of the first damselfly Lestes regina Théobald, 1937 from Monteils (Gard, France) supports the identity of late Eocene age of this outcrop with the historical outcrop of Célas, type locality for the type series of this species. Lestes regina is also documented from the late Eocene Isle of Wight basin, confirming the presence of significant contacts between this southern area and the anglo-Parisian lacustrine basin at that time. Nearly all the Eocene and Oligocene fossil Lestes from Western Europe have a particular character, viz. the presence of a supplementary row of cells between the veins MP and CuA. This character is much less frequent in extant Lestes and is still unknown among Neogene representatives of the genus.